Analysis of Sodium Content and Estimated Daily Intake from Shellfish Consumption: Case Study in Banda Aceh - Ardila, Mutia; Kurniawan, Rizky; Kurniawan, Hadi; Harahap, Muhammad R. (Universitas Tadulako, 2025)
This study aims to analyze sodium (Na) levels and estimate the daily intake (EDI) from the consumption of three shellfish species: blood mussels (Anadara granosa), kepah (Polymesoda erosa), and nipah (Geloina coaxans) obtained from Al Mahira Market and the Alue Naga area in Banda Aceh. Sodium concentrations were determined using Atomic Absorption Spectrophotometry (AAS). The results showed that sodium levels ranged from 1186 to 4656 mg/kg (wet weight). The highest EDI was found in blood mussels from Al Mahira Market at 0.997 mg/kg body weight/day (3.489% of the recommended daily sodium intake). In comparison, the lowest was observed in nipah clams from the exact location at 0.247 mg/kg body weight/day (0.866%). Overall, sodium intake from shellfish in both locations contributed less than 5% of the daily sodium limit. These findings indicate that shellfish consumption poses a low sodium-related health risk, although frequent or high intake may still contribute to long-term hypertension risk.